PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE MARKET PLACE ACTIVITY PADA MATA PELAJARAN FIKIH DI KELAS VIII MTS AL-JAM’IYATUL WASHLIYAH TEMBUNG - Nurhidayah, Nurhidayah; Sinaga, Ali Imran; Sirait, Arlina (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The study was done to learn (1) the results of a student’s study before cutting Market Place Activity on a fictional class in the VIII MTs Al-Jam’iyatul Washliyah Tembung. (2) Student learning after using the method of Market Place Activity at careful subject class in the VIII MTs Al-Jam’iyatul Washliyah Tembung. It’s a class-action research. The subject of research this is the class VIII MTs Al-jam’iyatul Washliyah Tembung, which consists of 32 students. Based on the study that: (1) pre-test results of only 5 students were able to achieve a low grade, while 27 other students remained incomplete, the average value was obtained 60 at a 16% percentage. (2) On the I cycle it is capable of achieving a simple sharpness 9 students, while 23 of the other students have not yet achieved a sharp score with a 68 rating rate average of 28%. Then in the II cycle the students who have been able to achieve a sharp score of 28 students while the unfinished students constitute 4 students with an average score of 80 and a rating percentage of 87%. Based on the above then the method of Market Place Activity can improve students learning results on fixed subjects.Keywords: Study Results; Market Place Activity